An Examination of the Economic and Social Impacts of Corporate Innovation and Interventions - Maestracci, Aria (Research Parks Publishers, 2023)
There has been a major shift in the concept of innovation as one of the key factors of production, as a factor that drives and sustains a company's productivity and competitiveness, of innovation as a key factor of production. Despite the fact that the importance of innovation continues to grow, it is observed that existing studies have produced a variety of results regarding the factors that drive firm-level innovations, despite the increasing importance placed on innovation. Throughout the world, there are a number of factors that drive innovation in a company, whether it is in the service sector or in the manufacturing sector, and this study examines some of these factors. A number of research results suggest that certain aspects of the business environment, such as policy instability, legal institutions, corruption, and informal competition, have a negative impact on the introduction of non-technological innovations, as indicated in the research findings. Additionally, the results indicate that both technological and non-technological innovations are positively impacted by formal training, multinational technology companies, and research and development. These effects have both marginal and additional effects. The paper aims at providing practical implications for firm managers and policymakers around the world concerning how the business environment can be improved in order to make it more conducive to innovative activity at the firm level, thus making it a more conducive business environment for generating innovations at the firm level.